On the acquisition of the syntax of Romance - Gavarró, Anna (Language acquisition & language disorders ;, 2018)
"This volume presents eleven papers on the acquisition of Romance, most of them presented at the Romance Turn VIII, held in Bellaterra in September, 2016. The first part of the volume is devoted to passives and related constructions: subject- and object-experiencer predicates. The results unveil domains in comprehension in which children are adult-like, while in other domains there is delay - it is a challenge for current theoretical proposals to encompass all of these results. The second part of the volume focuses on the TP-field: clitics and negation. The third part deals with the CP-field, with topics such as backward anaphora, subjects and the left periphery, and recursiveness. The volume includes studies carried out on a variety of populations: typically developing children, bilinguals, children with Autism Spectrum Disorders and Specific Language Impairment, and heritage speakers, with a view to a general theory of language acquisition"--